TRANSFORMATION OF MSMEs MARKETING STRATEGY THROUGH THE IMPLEMENTATION OF QRIS AS A DIGITAL INNOVATION - Fatimah Nur Nisa; Anita Sumelvia Dewi (SOSIOEDUKASI, 2025)
Micro, Small and Medium Enterprises (MSMEs) play an essential role in the Indonesian economy because they are not influenced by foreign factors and depend on local supply chains. Adapting to changing market conditions is necessary for these businesses to thrive, especially in today's digital age where smartphones and social media are widely used by Indonesians. This socialisation aims to increase awareness of the importance of digitalisation of payment systems in MSMEs as a means of digital marketing. By using a descriptive qualitative approach and community service carried out through education and socialisation as well as direct assistance in making QRIS will help MSMEs in strengthening their marketing strategies in attracting consumer buying interest for ease of transactions compared to competitors who use conventional payment services. Data collection techniques through observation, interviews, and documentation with MSME players in Kediri City. The results show that education about QRIS and consumer protection encourages MSME players in marketing strategies that need to be carried out in the era of cashless society and supports the professionalism of MSMEs.